2017
DOI: 10.7205/milmed-d-16-00344
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Circumference Body Composition Measurements and Eight-Point Bioelectrical Impedance Analysis to Dual Energy X-Ray Absorptiometry to Measure Body Fat Percentage

Abstract: There was good agreement between the three methods assessed in this study. Both waist circumference and gender had an effect on the accuracy of the DSM-BIA and CM measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…However, unlike in our study, the study protocol followed by Combest et al did ensure the hydration status of participants. To the extent that some participants were not well hydrated, this could impact the accuracy of our gold standard BF% estimates by adding random error to the measurement . Second, various studies have reported that older military personnel are at a higher risk of overweight/obesity compared with those in younger age categories .…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…However, unlike in our study, the study protocol followed by Combest et al did ensure the hydration status of participants. To the extent that some participants were not well hydrated, this could impact the accuracy of our gold standard BF% estimates by adding random error to the measurement . Second, various studies have reported that older military personnel are at a higher risk of overweight/obesity compared with those in younger age categories .…”
Section: Discussionmentioning
confidence: 90%
“…A study by Combest et al in active‐duty military personnel reported that BF% by BIA had excellent agreement with DXA in both men ( n = 31; intraclass correlation coefficient = 0.89; 95% CI: 0.78‐0.94) and women ( n = 45; intraclass correlation coefficient = 0.93; 95% CI: 0.87‐0.96). However, unlike in our study, the study protocol followed by Combest et al did ensure the hydration status of participants. To the extent that some participants were not well hydrated, this could impact the accuracy of our gold standard BF% estimates by adding random error to the measurement .…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations